Hepatocellular carcinoma in Child's A cirrhosis: a retrospective analysis of matched pairs following liver transplantation vs. liver resection according to the intention‐to‐treat principle. (31st October 2013) - Foltys, Daniel; Zimmermann, Tim; Kaths, Moritz; Strempel, Mari; Heise, Michael; Hoppe‐Lotichius, Maria; Weiler, Nina; Scheuermann, Uwe; Ruckes, Christian; Hansen, Torsten; Pitton, Michael; Otto, Gerd
Abstract This is the first matched pair analysis on the puzzling clinical problem of whether to perform liver transplantation (LT) or liver resection (LR) for Child's A hepatocellular carcinoma (HCC) patients. A total of 201 patients diagnosed with HCC and Child's A liver cirrhosis were treated with LT transarterial chemoembolization (TACE) or LR between 1998 and 2012. To achieve the most accurate study design, two groups of 57 patients were matched retrospectively according to their tumor characteristics detected by the initial computerized tomography (CT) scan. Sixteen of 57 LT candidates were not transplanted due to tumor progress during pre‐treatment (TACE). Nevertheless, the retrospective analysis of the matched pairs according to the intention‐to‐treat principle resulted in a better five‐yr overall survival (OS) rate of 54.3% for the group of LT candidates compared with 35.7% for those receiving LR (p = 0.19). In patients meeting the University of California, San Francisco (UCSF) criteria, five‐yr OS reached 58.4% after LT and 45.1% after LR (p = 0.56). For Milan criteria (MC) patients, LT resulted in 57.9% and LR in 42% five‐yr OS rate (p = 0.29). In conclusion, the finding of a better OS rate in LT was not statistically significant. There was also a selection bias in favor of LT, which may have influenced the OS. Therefore, particularly in regard to organ scarcity, LR remains a viable treatment option for respectable HCC in Child's A cirrhosis.